Pengembangan Keterampilan Dasar Bagi Peserta Didik Untuk Mempersiapkan Era Society 5.0 - Ulfiani Mabruroh (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
An aging society has caused several health and social problems in Japan. Therefore, in order to overcome the current problems and to prevent future problems, Japan has embarked on a human-centered transformation, namely Society 5.0 which is experienced not only domestically but also worldwide. This change requires everyone, especially the younger generation to prepare themselves to survive and even lead it. There is a set of skills that must be mastered by students to achieve these goals, namely communication, leadership, reading comprehension, and curiosity. This paper aims to describe methods for developing these skills in elementary school students. The conclusion states that some of the methods actually complement each other, meaning that they can be applied interchangeably in a school setting.